Local environments of SNe Ic and Ic-BL. Issue Volume 11:Issue A29B(2015) (27th October 2016) - Selsing, Jonatan; Christensen, Lise; Thöne, Christina; Modjaz, Maryam
Abstract: We have observed the local explosion environments of a sample Type Ic and Type Ic-BL Supernove (SNe) selected from both targeted and non-targeted surveys using VLT/VIMOS in IFU-mode. It is believed that by probing the local surroundings of the parent stellar populations of these types of SNe, valuable information can be gained about the physical conditions, which affect the type of SNe produced. The different kinds of SNe produced are determined by the initial mass and metallicity of the stellar progenitor, as well as by the metallicity-dependent mass loss in the stellar winds at the end phase of their evolution and the interaction with a sufficiently close companion star.